Assessment of Work Productivity and Activity Impairment (WPAI) questionnaire for migraine with the help of a smartphone app - DOMINGUES, Renan Barros; PICON, Isabella Silva; VESCOVi, Julia; CHUNG, Gabriel; CABRAL, Felipe Teijeiro; BERTELLI, Ayrton Piassi; LEE, Annelise Akemi Higa; SILVA, Paulo Diego Santos (Arquivos de Neuro-Psiquiatria, 2020)
Background: Migraine is a major cause of disability, which affects many areas of life, including productivity at work. Measuring absenteeism and presenteeism resulting from migraine with the use of appropriate tools is essential for better understanding the impact of this disease. Objective: The aim of the present study was to assess the work impact of migraine using the Brazilian Portuguese version of Work Productivity and Activity Impairment (WPAI) questionnaire. Methods: This survey was carried out with the aid of a smartphone app (Dr Cefaleia for Doctors) containing the questionnaires: ID-Migraine, Headache Impact Test (HIT-6), and WPAI. The data were collected during a headache awareness event. Correlations were assessed between migraine impact (HIT-6) with WPAI parameters: a) work time missed (absenteeism), b) impairment at work (presenteeism), c) overall work productivity loss (absenteeism+presenteeism), and d) activity impairment outside work. Results: Overall, 305 subjects with headache were interviewed and 167 were classified as having migraine. No significant differences in migraine impact according to sex (p=0.8) and modality of work were registered (p=0.8). Females had significantly higher absenteeism score (p<0.001), but presenteeism score was not significantly different between genders (p=0.3). WPAI absenteeism and presenteeism scores significantly correlated with migraine impact (HIT-6). Conclusions: The results suggest WPAI Brazilian Portuguese version was efficient in assessing migraine related work impact. The use of an app with validated questionnaires facilitates the conduction of migraine impact research in different populations, allowing a better understanding of the burden of this disease.
Keywords: Migraine Disorders; Headache, Presenteeism; Absenteism; Telemedicine